A systematic review of adaptive wildlife management for the control of invasive, non‐native mammals, and other human–wildlife conflicts. (6th February 2020) - Richardson, Suzanne; Mill, Aileen C.; Davis, Darryl; Jam, David; Ward, Alastair I.
Abstract: We are entering an era where species declines are occurring at their fastest ever rate, and the increased spread of non‐native species is among the top causes. High uncertainty in biological processes makes the accurate prediction of the outcomes of management interventions very challenging. Adaptive management (AM) offers solutions to reduce uncertainty and improve predictability so that the outcomes of interventions can continuously improve. We quantitatively assess the extent to which AM is used for managing vertebrates, with a focus on invasive non‐native species (INNS). Using the Web of Science, we evaluated 3992 articles returned by the search terms 'adaptive management' or 'adaptive harvest management' against seven recommended elements of AM (engagement with stakeholders, defining objectives, forecasting and estimating uncertainty, implementing management, monitoring populations, adjusting management in response to monitoring, and improving forecasting and reducing uncertainty in response to monitoring populations). The use of AM for vertebrates was reported in 56 (1%) of the evaluated studies; including four for managing INNS. Of these, ten studies excluding INNS and no studies of INNS management implemented all seven recommended elements of AM. Those elements infrequently implemented were as follows: the use of analysis or models to forecast and represent uncertainty (44%) and the feedback of monitoring data to improve forecasting and reduce uncertainty (25%). Complete active AM has rarely been implemented and reported for managing INNS, despite the significant advantages it offers. Among studies purporting to have implemented AM, most did not use analyses or models to forecast and represent uncertainty, while most defined objectives, implemented management, and monitored populations. Improvements to ongoing control programmes and much broader adoption of the AM approach are required to increase the efficiency and success of INNS management campaigns and reduce their negative impacts on native species. Abstract : Species declines are occurring at their fastest ever rate, and the increased spread of non‐native species is among the top causes. High uncertainty in biological processes makes the accurate prediction of the outcomes of management interventions very challenging. Adaptive management (AM) offers solutions to reduce uncertainty and improve predictability so that invasive non‐native species (INNS) can be managed more effectively. We evaluated 3992 articles against seven recommended elements of AM (engagement with stakeholders, defining objectives, forecasting and estimating uncertainty, implementing management, monitoring populations, adjusting management in response to monitoring, and improving forecasting and reducing uncertainty in response to monitoring populations). The use of AM for vertebrates was reported in only 1% of the evaluated studies; only four studies were on managing INNS. Of these, ten studies excluding INNS and no studies of INNS management implemented all seven recommended elements of AM. Complete active AM has rarely been implemented and reported for managing INNS, despite the significant advantages it offers. Improvements to ongoing control programmes and much broader adoption of the AM approach are required to increase the efficiency and success of INNS management campaigns and reduce their negative impacts on native species.